DAMPAK PERCERAIAN YANG TIDAK SESUAI DENGAN PROSEDUR PERUNDANG-UNDANGAN - Ramadhan Syahmedi Siregar (IAIN Padangsidimpuan, 2015)
Abstract: Divorce is a legal event, and then it should be an event carried out in accordance with rules of legal and judicial procedures. Otherwise it will result in lack recognized a divorce, this is in line with what is mandated in Law No. 1 of 1974 on article 38 and 39, which reads: